Design and Transient Studies on Multi-Terminal VSC-HVDC Systems Interconnecting Offshore Wind Farms - Muniappan, Mohan; Vittal, K. Panduranga (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2019)
In recent years, offshore wind energy has increased significantly. The continuous increase in the offshore wind power generation level brings the requirement of the offshore wind farms (OWFs) integration with an AC grid. The multi-terminal (MT) voltage source converters (VSC)-based high voltage direct current (HVDC) transmission system is an emerging technology and also the best option to interconnect the large-scale OWFs to the AC grid. This paper presents the design, modeling, and control of MT VSC-HVDC transmission system linked offshore wind farms. Different cases of MT VSC-HVDC transmission systems are developed, and its simulation studies are carried out using PSCAD/EMTDC. The test results show the transient performance of the MT VSC-HVDC transmission systems under various AC and DC fault conditions. The studies also include the influence of wind variabilities as in the form of gust and ramp pattern during steady state and fault conditions.